Detecção de HPV e avaliação do índice de proliferação celular entre carcinomas espinocelulares e carcinomas verrucosos de boca - SPÍNDULA FILHO, José Vieira de (2006)
Squamous cell carcinoma (SCC) is the most common malignant neoplasm of the bucal cavity, and one of its variants is verrucous carcinoma (VC), of low degree malignancy. The diagnosis of VC is difficult from the clinical as well as from the histopathological point of view, and an effective diagnosis is vital when deciding on the treatment and prognosis of this tumor. The aim of this research was to evaluate cell proliferation and investigate the presence of HPV in spindle cell carcinoma of the mouth so as to check for possible differences in the aetiopathogenesis and biological behavior of these lesions. Forty-seven samples were selected and divided as follows: 39 SCCs, 8 VCs and 9 control (CT). Cell proliferation was qualitatively evaluated according to the location of the expression of the immunomarker in the cell and epithelium layers and by quantitatively considering the percentage of positive cells expressed. The analysis of HPV+ carcinomas was undertaken by means of the polymerase chain reaction (PCR), having GP5+/6+ as primers for identification of the virus. The qualitative analysis showed that the immunomarking in the VC as well as in the control group was concentrated mainly in the basal and parabasal layers and the counting of the positive cells at the base of the epithelium showed a significant statistical difference in the expressions of all three markers (p<0,05). The quantitative analysis of the cell proliferation markers was calculated by means of the Mann-Whitney and Kruskal Wallis tests and through the Pearson and Spermans correlation. They pointed to differences between the SCC and VC groups for the PCNA and cyclin B1 markers (p<0,05). On considering the three groups, it was proved that there was a positive correlation between Ki67 and the cyclin B1 (r=0,56) but not between the PCNA and the Ki67. The PCNA immunomarking was greater in the control group (average=100%), and the Ki67 showed itself to be effective as a proliferation cell marker although it showed no significant difference between the carcinoma variants. Whereas the cyclin B1 showed a significant difference in the comparison between the SCC and the VC groups (p<0,05), and a positive correlation to the extent that the histological grading of the malignancy (WHO model) of the carcinomas increased (r=0,44). All tumor samples were negative for HPV. Although the lesions showed different biological behaviors, the cell proliferation index in both types of mouth carcinoma was higher than in the control group, as shown by the analysis of the Ki67 and cyclin B1 markers. On considering the total sample of carcinomas, independently of the tumor variety, cyclin B1 showed a positive correlation with the histological degree of malignancy according to WHO. There is a need for further study to be carried out in the field of cell proliferation and detection of HPV especially with regard to VC, because it is a rare variant of SCC.